THE EFFECT OF RED DRAGON FRUIT (HYLOCEREUS POLYRHIZUS) JUICE ON TOTAL CHOLESTEROL LEVEL IN WOMEN - Arista Dhea Maharani; Hari Saktiningsih (Universitas Medan Area, 2022)
Cholesterol is a component of fat/lipid substances in the form of free and esters with fatty acids. The excessive cholesterol in the blood can form deposits on the walls of blood vessels, causing atherosclerosis. Anthocyanins and tocotrienol compounds in red dragon fruit can suppress the formation of cholesterol in the body. The type of research used was an experiment with a pretest and posttest approach. The study used 1 dose of 2.86g/KgBW for 14 days. The samples used were the women members of PKK RT 04 RW 16 Mojosongo Surakarta totaling 18 people. The average total cholesterol level before treatment in this study was 237.28 mg/dl and after treatment 222.89 mg/dl. This study was tested using the Shapiro-Wilk test. It was known that the data were normally distributed (p>0.05), Paired t-test data obtained a significance result of 0. 012 (p<0.05). It can be concluded that Ho is rejected, which means that there is an effect of giving red dragon fruit juice (Hylocereus polyrhizus) on total cholesterol levels in women.